Reading Hopkins after Hubble: The Durability of Ignatian Creation Spirituality - Hamm, M. Dennis (Horizons, 2014)
The Victorian poet Gerard Manley Hopkins already demonstrated a special sensitivity to nature as a young Anglican. But his conversion to Catholicism, followed by his formation as a Jesuit, nurtured a creation spirituality that moved him from the rather cold view of the cosmos typical of his Victorian era to a vibrant sense of God intimately revealed in nature. This new sense of being a creature involved in an intimate personal relationship with the Creator comes from Hopkins' appropriation of the creation spirituality of Ignatius of Loyola. After reviewing the evolution of worldviews from the medieval synthesis melded with the Newtonian mechanical model (the Victorian picture) to our contemporary cosmic "story," this article then samples poems that illustrate the creation spirituality that Hopkins absorbed from Ignatius' vision. This vision is remarkably in tune with the new sense of the place of the human creature in the cosmic story that the sciences now tell regarding the emergence of matter, life, and persons.